DIAGNOSIS AND PREVENTION OF TORCH INFECTION IN PREGNANT WOMEN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Intrauterine infections (IUI) are a group of infectious and inflammatory diseases of the fetus and young children that are caused by various pathogens, but are characterized by similar epidemiological parameters and often have the same type of clinical manifestations. Congenital infections develop as a result of intrauterine (anteuterine/or intranatal) infection of the fetus. IUIs are serious diseases and largely determine the infant mortality rate. The relevance of the problem of congenital infections is due not only to significant peri- and postnatal losses, but also to the fact that children who have suffered severe forms of congenital infection very often develop serious health problems, often leading to disability and a decrease in the quality of life in general. Taking into account the widespread prevalence and seriousness of the prognosis, it can be concluded that the development of highly accurate methods of early diagnosis, effective treatment and effective prevention of congenital infections is one of the priority tasks of modern pediatrics.